Milan makes it to the big leagues: A financialized growth machine at work - Anselmi, Guido; Vicari, Serena (European urban and regional studies, 2020)
This article analyses the production of urban space in the globalizing city of Milan, Italy. The authors present the evolution of a 30-year development process in a semi-central area of the city known as Garibaldi Porta Nuova, contrasting present and past conditions. Initial attempts to develop the area began in the early 1980s but came to nothing; a previous study of the same area attributed that failure to the inability of fragmented local political elites to coalesce into an effective pro-growth coalition. In the early 2000s, a new coalition of political and economic actors, in particular financial and real estate interests, revived the process of regeneration and drove construction of a large-scale mixed-use project. This article offers an account of the process in terms of both the internal dynamics of the local coalition and the contextual and institutional factors framing the bargaining of political and economic elites over the development process. We use two theoretical frameworks – growth machine theory and regime theory – to assess the distribution of power and resources. Our analysis indicates that the outcome is the result of a specific growth machine fuelled by international capital, and that changes in the intergovernmental system in Italy induced local political elites to accommodate the requirements of international investors.